Gastric cancer perforation - D'Auria, Agustín E. (Cirugía del Uruguay, 1977)
13 patients with perforation were ·observed among 1732 gastric canc.ers during a 21 year period at the Hospital de Clinicas of Montevideo. All the patients were old-aged. They were admitted with different conditions, sorne typical of gastroduodenal perforation, sorne pseudo-obstructive and sorne pointing to other acute abdominal affections. Simple closure of perforation was followed by a 33 %, gastric fistulization by 100% and gastrectomy by 25 % mortality. General immediate mortality was in the order of 38,4 % . A 13 years 4 months survival after gastrectomy is reported.